The DNA polymerase III holoenzyme contains γ and is not a trimeric polymerase - Dohrmann, Paul R. (Nucleic Acids Res, 2016)
There is widespread agreement that the clamp loader of the Escherichia coli replicase has the composition DnaX(3)δδ’χψ. Two DnaX proteins exist in E. coli, full length τ and a truncated γ that is created by ribosomal frameshifting. τ binds DNA polymerase III tightly; γ does not. There is a controversy as to whether or not DNA polymerase III holoenzyme (Pol III HE) contains γ. A three-τ form of Pol III HE would contain three Pol IIIs. Proponents of the three-τ hypothesis have claimed that γ found in Pol III HE might be a proteolysis product of τ. To resolve this controversy, we constructed a strain that expressed only τ from a mutated chromosomal dnaX. γ containing a C-terminal biotinylation tag (γ-C(tag)) was provided in trans at physiological levels from a plasmid. A 2000-fold purification of Pol III* (all Pol III HE subunits except β) from this strain contained one molecule of γ-C(tag) per Pol III* assembly, indicating that the dominant form of Pol III* in cells is Pol III(2)τ(2) γδδ’χψ. Revealing a role for γ in cells, mutants that express only τ display sensitivity to ultraviolet light and reduction in DNA Pol IV-dependent mutagenesis associated with double-strand-break repair, and impaired maintenance of an F’ episome.